Valorization of Russian Sturgeon (Acipenser gueldenstaedtii) Processing Waste: Sustainable Enzymes for Biotechnological Applications Contributing to the Circular Economy - Clara Liébana; Juana Cristina del Valle; María Victoria Laitano; Ivana Soledad Friedman; Yamila Eliana Rodriguez; Alejandro Gabriel Perretta-Noschesi; Ignacio Quartiani-Zubieta; Analia Verónica Fernández-Gimenez (Circular Economy and Sustainability, 2026)

Chronic heat stress reshapes Russian sturgeon innate immune response to Aeromonas hydrophila challenge - Marcio Aversa-Marnai; Alejandro Perretta; Paula Céspedes; Ignacio Quartiani; Daniel Conijeski; Mariela Bollati-Fogolin; Andrea Villarino; Valeria Silva-Álvarez; Ana María Ferreira (Fish & Shellfish Immunology, 2025)

Threatened conservation scientists: The aftermath of an eye-opening publication on rewilding - María de las Mercedes Guerisoli; Mauro I. Schiaffini; Pablo Teta; Alejandro E.J. Valenzuela; Patricia Mirol; Javier Nori; Guillermo E. Defossé; María Marcela Godoy; Pablo Krieger; Tomás Withington; María G. Agostini; Christopher B. Anderson; et al. (Biological Conservation, 2023)

Impressions of the scientific training in fishery and aquaculture biotechnology in Mar del Plata, Argentina: Communication, networking, and multidisciplinary research - Ângelo Paggi Matos; Andressa Coimbra Pereira; Alejandro Perretta; Patricia Romero-Murillo; Luciana Melisa Del Gobbo; Emily Sol Garcia Martinez; Samuel Hilevski; Lucas Roberto Sepúlveda; Agustín Fernando Boan; Daniela Sartoni; Daiana Yanel Pereyra; Lucia García Martínez; et al. (Aquaculture, 2023)

Complete genome sequence and analysis of a novel lymphocystivirus detected in whitemouth croaker (Micropogonias furnieri): lymphocystis disease virus 4 - Andor Doszpoly; Győző L. Kaján; Rodrigo Puentes; Alejandro Perretta (Archives of Virology, 2020)
A novel lymphocystivirus causing typical signs of lymphocystis virus disease in whitemouth croaker ( Micropogonias furnieri ) on the coast of Uruguay was detected and described recently. Based on genetic analysis of some partially sequenced core genes, the virus seemed to differ from previously described members of the genus Lymphocystivirus . In this study, using next-generation sequencing, the whole genome of this virus was sequenced and analysed. The complete genome was found to be 211,086 bp in size, containing 148 predicted protein-coding regions, including the 26 core genes that seem to have a homologue in every iridovirus genome sequenced to date. Considering the current species demarcation criteria for the family Iridoviridae (genome organization, G+C content, amino acid sequence similarity, and phylogenetic relatedness of the core genes), the establishment of a novel species (“ Lymphocystis disease virus 4 ”) in the genus Lymphocystivirus is suggested.

Phenotypic, molecular and pathological characterization of motile aeromonads isolated from diseased fishes cultured in Uruguay - Alejandro Perretta; Karina Antúnez; Pablo Zunino (Journal of Fish Diseases, 2018)
Information about motile aeromonads from aquaculture systems of the Neotropical region is scarce. The aim of this study was to characterize motile Aeromonas isolated from ornamental and consumable fishes cultured in Uruguay. Biochemical and molecular methods were used for species identification. Antimicrobial susceptibility and the presence of virulence genes were evaluated. Genetic diversity was analysed by rep‐ PCR , and virulence of the most representative isolates was determined by calculating the fifty lethal dose in experimentally challenged fish ( Australoheros facetus ). Aeromonas hydrophila and A. veronii were the most prevalent identified species (38.2% and 32.4%, respectively), whereas A. allosacharophila , A. bestiarium , A. caviae and A. punctata were less prevalent. This study constitutes the first report of these last four species in Uruguay. All isolates were resistant to at least three antimicrobials, and 82.3% of them showed multidrug resistance. Virulence genotypes were correlated with the Aeromonas species and haemolytic activity. The genotype act +/ alt +/ ast +/ ela +/ lip + was the most prevalent (26.5%). A correlation between virulence genotypes and Aeromonas species was found. A. punctata showed a clonal structure according to rep‐ PCR analysis, whereas other species showed high genetic diversity. The number of virulence genes of the isolates was related with virulence according to the experimental challenge assays.